Static tensile test of materials - Beh, Jude Anthony Zhao Hong (2018)
In this Final Year Project, B027, titled Static Tensile Test of Material, the student was responsible in determining the mechanical properties of Aluminium 6061-T6. A static tensile test was done to determine the desired mechanical properties. Unlike the similar project from previous batch, specimens were fabricated using milling machine method, instead of EDM wire cutting. The purpose is to verify whether different machine methods play a part in affecting the mechanical properties of the aforementioned material. Also, the student will verify the accuracy of using extensometer to extract strain reading as the results obtained after the test will be used to compare with previous year students, who used a similar method. Static tensile test is a fundamental method in which key mechanical properties are determined from a material specimen. These key mechanical properties are yield strength, ultimate strength, elongation at fracture and Young’s modules. In this FYP, Shimadzu AGX plus 10kN were used to perform the static tensile test on every specimen. Using the raw data extracted from each test result, the student will plot a stress-strain curve of Aluminium 6061-T6 for each specimen. Further analysis on the curve will be done when comparing them to the previous year student’s result. The objective of this project is to use specimens to do sequences of tensile test under 3 different types of feed rate of 0.5mm/min, 1.0mm/min and 1.6mm/min respectively. All the tensile tests were done while observing the standard test methods for tension testing of metallic materials under ASTM. The ASTM edition that the student followed was E8/E8M. The machine methods used was the traditional milling method.